PATHOGENITY TESTING OF THE MUSHROOMS Trichoderma spp. SOME PLANTATION LAND IN CONTROLLING Fusicoccum sp DISEASE OF TOBACCO PLANT - Novita, Aisar; Lubis, Efrida; Phuoc, Le Huu; Phuoc, Le Huu (International Journal of Biosciences and Biotechnology; Vol 10 No 2 (2023): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2023)
Trichoderma is a soil saprophytic fungus that is naturally parasitic and attacks many types of plant disease-causing fungi or has a broad spectrum of control. This study aims to obtain superior isolates of the antagonist fungus Trichoderma sp from several plantations. This study used a non-factorial completely randomized design consisting of seven treatments with three replications. The treatments tested were: No Treatment (To); Trichoderma sp isolate from Langkat rubber (T1) Trichoderma sp isolate from Palm Oil Langkat (T2), Trichoderma sp isolate from Cocoa Langkat (T3), Trichoderma sp isolate from Percut oil palm (T4), Trichoderma sp isolate from Karo Coffee (T5), Trichoderma sp isolates from Karo cocoa (T6) Parameters observed were identification of the fungus Trichoderma sp., pathogenicity test on tobacco plants and percentage of pathogen inhibition. The results of both macroscopic and microscopic identification of Trichoderma sp isolates from rubber plantations in Langkat area (T1) showed that the highest percentage of inhibition and pathogenicity tests against Pussicoccum sp disease of tobacco plants showed negative results (no necrotic spots).